(untitled) (Al Basirah, 2020)
The purpose of the research is an empirical study of the impact of difference of opinion of Hadith Scholars and Ahnaaf among the Jurists regarding disagreement of the reliable reporters in narrating hadīth on Pakistan Community. As Pakistan is the multi-jurisdictional community, hence number of opinions on any topic may confuse Pakistani mind and it perceives as one is derived from Hadith and other is based on juristic opinion. This confusion primarily prevailed due to negligence of difference of methodology among Muhaddithin and Jurists regarding acceptance or rejection of Ahaad Hadith. Therefore, the main objective of the researh is to elaborate the methodologies of both type of scholars but the study will be limited to the critical analysis of the difference of opinion on disagreement of the reliable reporters in narrating hadīth and its effect on Juristic Opinions derived from Sunnah. The research will primarily focus on view of Ahnaaf w.r.t Hadītth Scholars as hanafi fiqh is the most prevailing madhhab among the famous school of thoughts in Pakistan while Hadith Scholars are the main scholars of explaining Hadith Studies.